Hacia una metodología del aprendizaje en línea eficaz y personalizada. Estudio comparativo entre tres modelos de aprendizaje y su eficacia online - Mora, António Chenoll (2021)
Online education is an inevitable option in the current education system. If we ignore this point, it would be a mistake of effectiveness in learning. However, there are many models in which this modality is applied, and with designs that depend on very different conceptions connected to the final objectives of each institution and students. On the one hand, there are full online courses in which the objective is the massification (from the point of view of the massive educational right) of learning, online courses in which individualism is preferred to keep the quality, courses in b-learning regime and the complementary to face-to-face courses with technologically enriched courses. In this work, through the analysis of the different models from various perspectives (final objectives, materials, individualization, monitoring of learning, affective component, formal-informal, among others), we will see and analyze the three models developed by the Universidade Católica Portuguesa (Face-toface and technologically enriched education), Universidade Aberta (completely online and massive model) and by Universidad Antonio de Nebrija (Completely online and small groups model).